Loss of a Chance - Smith, Ben (Victoria University of Wellington Law Review, 1999)
Compensation for the loss of a chance has the potential to revolutionise the law of civil obligations as it is known today. It is an innovative theory of damages which was first conceived of at the beginning of this century. It effectively reformulates the damage as the loss of a chance to which the balance of the probabilities test still applies. This is consistent with the orthodox 'all or nothing' causation rule. 2 Its impact however has been delayed and it is only in the last decade that its challenge to orthodoxy has become clear. The primary purpose of this article therefore is to consider whether or not compensation for loss of a chance represents only a subset of the law of damages or its complete destruction.